Tantangan Komunikasi Antar-generasi dalam Lingkungan Kerja Organisasi Modern - Miftahul Jannah; Noniya Dewinta Anggi Ritonga; Muhammad Farhan (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In the era of globalization and technological transformation, modern organizations face intergenerational communication challenges due to a diverse workforce spanning from the baby boomer generation to Generation Z. This research highlights the complexity of differences in values, technological preferences, and management styles across generations. The analysis of intergenerational conflicts emphasizes the importance of effective conflict management, while the section on intergenerational communication outlines strategies to address these differences. Research findings identify variations in communication styles, perceptions of values, technological impacts, and conflicts. In conclusion, a profound understanding of intergenerational communication is crucial for productivity and a harmonious work environment in organizations with diverse generations.